2003
DOI: 10.1046/j.1365-2990.2003.00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of mRNA levels in the frontal cortex and the hippocampus in the basal state and in response to experimental brain injury

Abstract: Damage to the frontal cortex and to the hippocampus, both in terms of cell loss and neuronal dysfunction, is thought to underlie many of the neurological and behavioural consequences of traumatic brain injury (TBI). Several studies have indicated that the hippocampus is particularly susceptible to central nervous system insults, whereas the frontal cortex possesses relatively higher capacities for regeneration and plasticity. It has been postulated that dissimilarities in the gene expression profiles in these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 53 publications
1
22
0
1
Order By: Relevance
“…There have been several studies evaluating the effect of TBI on the time-dependent expression of specific genes (Bazan et al, 1995;Hayes et al, 1995;Marciano et al, 2002) and more recently, using microarray technology, expression of thousands of genes can be measured (Dash et al, 2004;Di Pietro et al, 2010;Natale et al, 2003;Raghavendra Rao et al, 2003;Rall et al, 2003;Truettner et al, 2005). The majority of the these studies evaluated gene expression only up to 24 h post-injury with the exception of that by Natale and associates who used microarray-based technology to evaluate gene expression 4,8,24, and 72 h post-injury (Natale et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies evaluating the effect of TBI on the time-dependent expression of specific genes (Bazan et al, 1995;Hayes et al, 1995;Marciano et al, 2002) and more recently, using microarray technology, expression of thousands of genes can be measured (Dash et al, 2004;Di Pietro et al, 2010;Natale et al, 2003;Raghavendra Rao et al, 2003;Rall et al, 2003;Truettner et al, 2005). The majority of the these studies evaluated gene expression only up to 24 h post-injury with the exception of that by Natale and associates who used microarray-based technology to evaluate gene expression 4,8,24, and 72 h post-injury (Natale et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…We compared the present mCCI data with previously published data from our laboratory using a more severe injury level. 53 It is important to note that our previous study employed a different microarray platform and detection chemistry, interrogated only a subset of the genes (*20%) contained on the RatRef-12 Illumina BeadArray, and the cortical tissues analyzed were distal to the injury site. We found that, of the 4429 genes in common on both arrays, moderate-to-severe and mild injury induced a significant change in mRNA expression level of 282 (6.4%) and 152 (3.4%) genes, respectively.…”
Section: Mtbi Pathway Analysismentioning
confidence: 99%
“…The transcriptional drivers behind these processes are being keenly elucidated, assisted by gene profiling studies that enable a large number of genes to be studied simultaneously. Typically, these studies are conducted using postmortem tissue obtained 4 -24 h after TBI and involve probing mRNA against cDNA arrays or gene chips (Rao et al, 1999;Kobori et al, 2002;Natale et al, 2003;Rall et al, 2003;Yoshiya et al, 2003;Keyvani et al, 2004;Di Giovanni et al, 2005). Together, these studies have confirmed that the trauma response is characterized by altered transcription of genes related to inflammation, apoptosis, neurotransmitter release, cell-cycle activation, gliosis, reactive oxygen metabolism, ionic homeostasis, and neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%